Imposture in Decline and Fall - Megías Rosa, Manuel (Revista Alicantina de Estudios Ingleses, 1995)
This article deals with an analysis of the characters in Decline and Fall, and the position they occupy in the novel. The main theme of the article is imposture. Paul Pennyfeather, the protagonist of the novel, goes from place to place, making a circular movement whose starting is also its end. Following Paul Pennyfeather, I try to demonstrate that most of the characters of the novel occupy a place that does not belong to them.